The NCP 5 – Tangible Fixed Assets: Study Application Case in Portugal - Pereira, Adalmiro Andrade (Advances in Social Sciences Research Journal, 2021)
2015 saw an important step in the accounting reform in Portugal. On September 11, 2015, the Accounting Standardization System for Public Administrations (SNC-AP) was approved through Decree-Law No. 192/2015, which revokes the Official Public Accounting Plan (POCP) and establishes an accounting standard aligned with international accounting standards. The development of this work is based on content analysis focused on Public Accounting Standard 5, NCP 5, which was broken down into the respective chapters of the regulations. In this way, to reach the objective of the study, work was developed on several themes, which are essentially based on the chapters of NCP 5. In this way, the topics covered are: Objectives, Scope and Definitions, Measurement, Recognition and Derecognition; and, in order to better contextualize and exemplify the practical application of the standard, we will find, at the end of this work, some practical situations.